2015
DOI: 10.5114/aoms.2013.34732
|View full text |Cite
|
Sign up to set email alerts
|

Experimental research In vivo evaluation of nerve guidance channels of PTMC/PLLA porous biomaterial

Abstract: IntroductionPeripheral nerve disruptions, frequently occurring during limb injuries, give rise to serious complications of patients recovery resulting from limitations in neural tissue regeneration capabilities. To overcome this problem bridging techniques utilizing guidance channels gain their importance. Biodegradable polymeric tubes seem to be more prospective then non-degradable materials – no necessity of implant removal and possibilities of release of incorporated drugs or biologically active agents that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…UPy-PC is a thermoplastic elastomer with PC soft blocks and hard blocks composed of interacting and phase-separated hydrogen bonding units based on the 2-ureido-[1H]-pyrimidin-4-one (UPy) motif [11]. PC is a degradable polyester, which has been successfully used in nerve and bone regeneration guidance [12,13]. UPy-modified polymers have been designed to serve as drug delivery vehicles, for example, in a porcine myocardial infarction model [14] and in a modular approach as a bioactive elastomeric material for tissue engineering [15].…”
Section: Introductionmentioning
confidence: 99%
“…UPy-PC is a thermoplastic elastomer with PC soft blocks and hard blocks composed of interacting and phase-separated hydrogen bonding units based on the 2-ureido-[1H]-pyrimidin-4-one (UPy) motif [11]. PC is a degradable polyester, which has been successfully used in nerve and bone regeneration guidance [12,13]. UPy-modified polymers have been designed to serve as drug delivery vehicles, for example, in a porcine myocardial infarction model [14] and in a modular approach as a bioactive elastomeric material for tissue engineering [15].…”
Section: Introductionmentioning
confidence: 99%
“…Many PTMC-based biomaterials have recently been investigated for applications in a broad range of implantable and/or resorbable devices. Chemically functionalized PTMC analogues with different pendant groups are derived from their corresponding cyclic monomers, demonstrating a diverse alteration of physicochemical properties. However, most of these analogues have been designed to be used as solutions, such as in drug/gene delivery, hydrogels, and antimicrobials. In contrast, composites of PTMC and copolymers, including trimethylene carbonate (TMC), have been studied for bulk applications such as scaffolds for bone, cartilage, and nerve regeneration. In addition, applications in blood vessels and as vascular stents are a targeted area of PTMC-based materials because the inherent flexible property of PTMC is well-suited for the required task. However, as with other hydrophobic biodegradable polymers that require concomitant administration of anticoagulants and antiplatelets for applications in blood-contacting devices, blood compatibility, and in particular the ability to suppress platelet adhesion, is indispensable for the PTMC-based materials. We have previously reported that no synthetic biodegradable polymers possessing high antithrombotic properties have been developed …”
Section: Introductionmentioning
confidence: 99%